AB0608 TOCILIZUMAB TREATMENT FOR LARGE VESSELS VASCULITIS: REAL LIFE PRELIMINARY EXPERIENCES. (June 2019) - righetti, giulia; Venerito, Vincenzo; Giannotta, Maria; Lopalco, Giuseppe; Giannini, Margherita; Cacciapaglia, Fabio; Coladonato, Laura; Iannone, Florenzo
Abstract : Background: IL-6r targeting therapy has been proven to be effective and safe in Giant Cell arteritis (GCA) as well in Takayasu arteritis (TA) in RCTs, probably because of the similar pathologic findings and vessel size (Large Vessel Vasculitis, LVV). However, real world data are scarce. Objectives: The aim of the study was to evaluate the effectiveness of Tocilizumab for LVV in real life settings. Methods: We retrospectively evaluated, from 2011 to 2017, the outcomes (including glucocorticoid dosage) in patients affected by LVV (according to 1990 aCR classification criteria) who received 8 mg/kg iv Tocilizumab (TCZ) monthly, due to the inadequate response to immunosuppressant. Demographic and clinical characteristics and laboratory findings were collected at baseline and consecutive follow up visits, over 52 weeks. Statistical analysis was performed using the GraphPad Software ver. 6.0 (San Diego CA USA) using appropriate tests. Results: We analyzed n.10 patients (6/10 GCA, 4/10 TA) with mean age (± SD) 56 ± 21 years and mean disease duration 41±38 months. Eight out of 10 patients were female. Over the entire observation period, 7/10 also received concomitant methotrexate (mean dose 12.8 ± 2.7 mg/week) while 2/10 received azathioprine (100 mg/day). Median (IQR) prednisone equivalent dose at baseline was 22.5 (10-25) mg/day. At baseline, median ESR was 49 (31-58) mm/h and median CRP level was 15.4 (1.95-28.53) mg/l. Upon TCZ treatment we observed a good disease control in absence of headache, fever and other LVV clinical signs through 52-week follow up. At 52 weeks, we observed a significant reduction of ESR down to 6.5 (2.75-12.25) mm/h as well as of CRP level, down to 1.5 (0.67-3.47) mg/l (p<0.001). A meaningful steroid sparing effect was also achieved as a significant reduction in prednisone dose down to 5 (1.87-6.25) mg/day (p<0.001). During the 52-week follow up period, 3 patients discontinued TCZ treatment for side effects: 1 for severe neutropenia (at 12 weeks), 1 for hemorrhagic pancreatitis (after 24 weeks), and 1 for diverticulitis (after 52 weeks). Conclusion: In our real life experience iv TCZ was effective and safe in LVV treatment, with a good disease control and a significant steroid-sparing effect. Our preliminary findings need to be confirmed in larger cohorts and prolonged follow-up. References: [1] Stone JH, Tuckwell K, Dimonaco S, Klearman M, aringer M, Blockmans D, Brouwer E, Cid MC, Dasgupta B, Rech J, Salvarani C, Schett G, Schulze-Koops H, Spiera R, Unizony SH, Collinson N. Trial of Tocilizumab in Giant-Cell arteritis. N Engl J Med. 2017Jul27;377(4):317-328. doi: 10.1056/NEJMoa1613849. PubMed PMID: 28745999. Disclosure of interests: giulia righetti: None declared, vincenzo venerito: None declared, maria giannotta: None declared, Giuseppe Lopalco Speakers bureau: SOBI, BMS, margherita giannini: None declared, Fabio Cacciapaglia: None declared, Laura Coladonato: None declared, Florenzo Iannone Consultant for: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, abbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Speakers bureau: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, abbVie, MSD, BMS, Novartis, Lilly, UCB outside this work